Cell-Free DNA to Detect Heart Allograft Acute Rejection - Agbor-Enoh, Sean; Shah, Palak; Tunc, Ilker; Hsu, Steven; Russell, Stuart; Feller, Erika; Shah, Keyur; Rodrigo, Maria E; Najjar, Samer S; Kong, Hyesik; Pirooznia, Mehdi; Fideli, Ulgen; et al. (Circulation (New York, N.Y.), 2021)
After heart transplantation, endomyocardial biopsy (EMBx) is used to monitor for acute rejection (AR). Unfortunately, EMBx is invasive, and its conventional histological interpretation has limitations. This is a validation study to assess the performance of a sensitive blood biomarker-percent donor-derived cell-free DNA (%ddcfDNA)-for detection of AR in cardiac transplant recipients. This multicenter, prospective cohort study recruited heart transplant subjects and collected plasma samples contemporaneously with EMBx for %ddcfDNA measurement by shotgun sequencing. Histopathology data were collected to define AR, its 2 phenotypes (acute cellular rejection [ACR] and antibody-mediated rejection [AMR]), and controls without rejection. The primary analysis was to compare %ddcfDNA levels (median and interquartile range [IQR]) for AR, AMR, and ACR with controls and to determine %ddcfDNA test characteristics using receiver-operator characteristics analysis. The study included 171 subjects with median posttransplant follow-up of 17.7 months (IQR, 12.1-23.6), with 1392 EMBx, and 1834 %ddcfDNA measures available for analysis. Median %ddcfDNA levels decayed after surgery to 0.13% (IQR, 0.03%-0.21%) by 28 days. Also, %ddcfDNA increased again with AR compared with control values (0.38% [IQR, 0.31-0.83%], versus 0.03% [IQR, 0.01-0.14%]; <0.001). The rise was detected 0.5 and 3.2 months before histopathologic diagnosis of ACR and AMR. The area under the receiver operator characteristic curve for AR was 0.92. A 0.25%ddcfDNA threshold had a negative predictive value for AR of 99% and would have safely eliminated 81% of EMBx. In addition, %ddcfDNA showed distinctive characteristics comparing AMR with ACR, including 5-fold higher levels (AMR ≥2, 1.68% [IQR, 0.49-2.79%] versus ACR grade ≥2R, 0.34% [IQR, 0.28-0.72%]), higher area under the receiver operator characteristic curve (0.95 versus 0.85), higher guanosine-cytosine content, and higher percentage of short ddcfDNA fragments. We found that %ddcfDNA detected AR with a high area under the receiver operator characteristic curve and negative predictive value. Monitoring with ddcfDNA demonstrated excellent performance characteristics for both ACR and AMR and led to earlier detection than the EMBx-based monitoring. This study supports the use of %ddcfDNA to monitor for AR in patients with heart transplant and paves the way for a clinical utility study. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02423070.